Syndromic intellectual disability: a new phenotype caused by an aromatic amino acid decarboxylase gene (DDC) variant - Graziano, Claudio; Wischmeijer, Anita; Pippucci, Tommaso; Fusco, Carlo; Diquigiovanni, Chiara; Nõukas, Margit; Sauk, Martin; Kurg, Ants; Rivieri, Francesca; Blau, Nenad; Hoffmann, Georg F.; Chaubey, Alka; et al. (Gene, 2015)
The causative variant in a consanguineous family in which the three patients (two siblings and a cousin) presented with intellectual disability, Marfanoid habitus, craniofacial dysmorphisms, chronic diarrhea and progressive kyphoscoliosis, has been identified through whole exome sequencing (WES) analysis. WES study identified a homozygous DDC variant in the patients, c.1123C>T, resulting in p.Arg375Cys missense substitution. Mutations in DDC cause a recessive metabolic disorder (aromatic amino acid decarboxylase, AADC, deficiency, OMIM #608643) characterized by hypotonia, oculogyric crises, excessive sweating, temperature instability, dystonia, severe neurologic dysfunction in infancy, and specific abnormalities of neurotransmitters and their metabolites in the cerebrospinal fluid (CSF). In our family, analysis of neurotransmitters and their metabolites in patient's CSF shows a pattern compatible with AADC deficiency, although the clinical signs are different from the classic form. Our work expands the phenotypic spectrum associated with DDC variants, which therefore can cause an additional novel syndrome without typical movement abnormalities.
Gesehen am 28.09.2020